PERCEIVED QUALITY, BRAND AWARENESS, DAN BRAND LOYALTY TERHADAP OVERALL BRAND EQUITY PADA KONSUMEN LUWAK WHITE KOFFIE DI JAKARTA - DENNIS SANTOSO; KLEMENS WEDANAJI PRASASTYO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to know the influence of perceived quality, brand awareness, and brand loyalty to brand equity overall at Luwak White Koffie consumer in Jakarta. This study was also conducted to improve the results of previous studies. The population of this study are male and female respondents who live in DKI Jakarta and who buy Luwak White Koffie at least 2 times a month. Researchers chose as many as 160 respondents as a sample of this study using purposive sampling and data collected using questionnaires. This research uses Structural Equation Modeling. The results of this study indicate that brand awareness has an influence on brand loyalty and there is influence between brand loyalty to brand equity overall in Luwak White Koffie consumer in Jakarta while there is no perceived quality influence on brand loyalty at Luwak White Koffie consumer in Jakarta.